The Effect of Metronome Pacing on Gait in Healthy Subjects - Mayberry, Kristina <1957> (Alma Mater Studiorum - Università di Bologna, 2014)
The complex process of gait is rendered partially automatic by central pattern generators (CPGs). To further our understanding of their role in gait control in healthy subjects, we applied a paradigm of anti-phase, or syncopated, movement to gait. To provide a context for our results, we reviewed the literature on in-phase, or synchronized, gait. The review results are as follows. Auditory cueing increased step/stride rate for older subjects, but not younger. Stride rate variability decreased for younger subjects, perhaps because the metronome’s cue acted as a temporal ‘anchor point’ for each step. Step width increased in half of the treadmill studies, but none of the overground ones, suggesting a cumulative effect of the attentional demands of synchronizing gait while on a treadmill. Time series analysis revealed that the α exponent was the most sensitive parameter reported, decreasing toward anti-persistence in almost all cued-gait studies. This project compares in-phase (IN) and anti-phase gait (ANTI) in young and old healthy subjects. We expected gait to be less disrupted during ANTI trials at preferred speed, when the facilitating effect of CPGs would be strongest. The measures step time variability, jerk index, and harmonic ratio quantified gait perturbation: none indicated that ANTI was easiest at preferred walking speed. Surprisingly, the gait of older subjects was no more perturbed than that of younger subjects. When they successfully matched the pace of the beat, they unwittingly synchronized to it. The temporal relationship of their steps to the beat was the same in the IN and ANTI conditions. Younger subjects, visibly struggling during ANTI trials, were able to walk in syncopation. This result suggests that cognitive resources available only to the younger group are required to resist synchronizing to the beat.